Psychosocial effects of Brazilian Truth Commission - (:unkn) unknown (Pontificia Universidad Católica del Perú, 2024)
A Truth Commission (TC) was carried out in Brazil (2012-2014) to investigate human rights violations perpetrated by state agents, especially during the military dictatorship (1964-1985). TCs are supposed to help societies on the reconstruction of social ...
Keywords: Comisión de la verdad; Efectos psicosociales